A heterojunction photoelectric catalyst and preparation method thereof

Through co-precipitation method and thermal annealing treatment, the full two-dimensional p-n-type heterojunction catalyst SnO2-x/g-C3N4 was prepared, which solved the problem of low catalytic activity of existing photoelectric catalysts in the carbon dioxide reduction process, achieved efficient photogenerated charge separation and carrier migration, and significantly improved the CO2 reduction conversion performance.

CN115896854BActive Publication Date: 2025-04-15INST OF COAL CHEM CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211573261.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-04-15
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

During the carbon dioxide reduction process, existing photoelectric catalysts have poor visible light response and high photogenerated charge recombination rate, resulting in low catalytic activity.

Method used

通过共沉淀法和热退火处理,原位复合得到片状g-C3N4和层状氧化亚锡的全二维p-n型异质结催化剂SnO2-x/g-C3N4,优化其结构和比表面积,增强相互作用和反应活性。

Benefits of technology

The photogenerated charge separation efficiency is improved, the carrier migration rate is enhanced, and the catalytic performance is improved. Especially in the reduction and conversion of CO2, the ratio and selectivity of CO to H2 in synthesis gas is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115896854B_ABST
    Figure CN115896854B_ABST
Patent Text Reader

Abstract

The invention discloses a heterojunction photoelectric catalyst and a preparation method thereof, belonging to the technical field of photoelectric catalytic reduction of carbon dioxide. The catalyst structural formula is SnO 2‑x / g‑C3N4, which is a fully two-dimensional configuration. The preparation method is to dissolve Na2C2O4 in deionized water, dissolve SnCl2·2H2O in concentrated hydrochloric acid, and then mix the two to obtain a mixed solution; add an aqueous solution of g‑C3N4 to the mixed solution for coprecipitation; wash and dry the precipitated product; grind the dried product into powder, calcine and decompose to obtain a layered catalyst. By combining the coprecipitation method with thermal annealing treatment, a fully two-dimensional p‑n type heterojunction catalyst composed of flaky g‑C3N4 and layered stannous oxide is obtained, which provides an additional built-in electric field to accelerate the migration rate of carriers, improve the efficiency of photogenerated charge separation, increase the carrier diffusion channel, and provide more active sites for the adsorption and activation of C=O bonds. Under the photoelectric coupling energy field, CO2 is catalytically reduced to synthesis gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoelectric catalytic reduction of carbon dioxide, and in particular relates to a heterojunction photoelectric catalyst and a preparation method thereof. Background Art

[0002] Carbon dioxide is the main gas causing the greenhouse effect. Its excessive emission has serious harm to human health and the living environment. Therefore, it is of great significance to study a pollution-free and efficient catalyst for reducing carbon dioxide. Among various methods for reducing carbon dioxide, photoelectrocatalysis integrates the advantages of photocatalysis and electrocatalysis. Its reaction conditions are mild, sunlight provides additional charges to reduce external energy input, and the applied electric field improves the separation efficiency of photogenerated charges. It is a very promising green and environmentally friendly method for converting carbon dioxide into synthesis gas. However, research on photoelectrocatalytic reduction of carbon dioxide is still in its early stages, and the reaction pathway is similar to that of a single catalytic reaction. The development of a photoelectrocatalyst that is efficient, stable, has excellent light absorption properties, fast transfer of photogenerated electrons, and high product selectivity is the current main research goal.

[0003] So far, g-C3N4, as an n-type semiconductor, has attracted extensive attention from many researchers due to its suitable valence band structure, thermal stability and chemical stability. However, its poor response to visible light and high recombination rate of photogenerated charges reduce the catalytic activity of photoelectric coupled reduction of CO2. Stannous oxide is a p-type semiconductor with an adjustable band gap structure and is widely used in photocatalytic degradation of pollutants. Patent CN110743598A prepared porous carbon nitride / tin / stannous oxide catalyst for the degradation of RhB by calcining and photodepositing porous carbon nitride and stannous chloride dihydrate. The ternary heterojunction prepared by this technology is based on porous carbon nitride. Compared with two-dimensional layered carbon nitride, it is not conducive to its interaction with other semiconductor materials to form a heterojunction. In addition, the low specific surface area is not conducive to the adsorption and activation of reactant molecules. At the same time, this technology first obtains PCN / SnO through two-step calcination, and then obtains PCN / Sn / SnO through photodeposition. The preparation method is relatively cumbersome, and the third step is to insert Sn between PCN and SnO through photodeposition, which has poor controllability. Patent CN113751045A obtains g-C3N4 / SnO2 nanoparticle heterojunction by mixing and stirring SnO2 octahedron and g-C3N4 nanosheets, which is used in the field of photocatalytic hydrogen production. This technology first prepares two semiconductors, and then physically mixes them to avoid the agglomeration of SnO2 particles. The contact resistance between g-C3N4 and SnO2 in the obtained heterojunction is large, which is not conducive to the transmission of photogenerated carriers and restricts the catalytic performance of the heterojunction. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes a heterojunction photoelectric catalyst and a preparation method thereof, and the technical scheme thereof is as follows:

[0005] A heterojunction photoelectric catalyst, the structural formula of the catalyst is SnO 2-x / g-C3N4; the catalyst is a fully two-dimensional structure, namely SnO 2-x Both g-C3N4 are two-dimensional sheets.

[0006] The present invention also provides a method for preparing the heterojunction photoelectric catalyst, which specifically comprises the following steps:

[0007] (1) Na2C2O4 is dissolved in deionized water, SnCl2·2H2O is dissolved in concentrated hydrochloric acid, and then the two are mixed to obtain a mixed solution; an aqueous solution of g-C3N4 is added to the mixed solution for co-precipitation; and the precipitated product is washed and dried.

[0008] Preferably, the g-C3N4 is prepared by calcining urea at 400-550°C for 2-4h and then cooling and grinding. The specific surface area of ​​g-C3N4 prepared by using urea as raw material is increased by 3-4 times compared with that prepared by using melamine as raw material. The larger specific surface area can not only enhance the bonding strength with SnO 2-x interaction, reducing the contact resistance between the two semiconductors in the heterojunction; it can also provide more active sites and reaction sites for the reaction.

[0009] Preferably, the aqueous solution of g-C3N4 is obtained by dissolving g-C3N4 in deionized water and uniformly dispersing it by ultrasonication.

[0010] Furthermore, the mass ratio of Na2C2O4 to SnCl2·2H2O is (2-5):3, and Sn(OH)2 can be obtained by co-precipitation of the two; heterojunction catalysts with different composite ratios can be obtained by adjusting the addition amount of SnCl2·2H2O.

[0011] Furthermore, the mass ratio of g-C3N4 and SnCl2·2H2O is 1:(2-6).

[0012] Preferably, the washing is performed by washing with deionized water and anhydrous ethanol for several times.

[0013] Preferably, when the aqueous solution of g-C3N4 is added to the mixed solution, stirring is performed while adding. More preferably, the stirring time is 0.5-1h. 2-x By adding g-C3N4 during the co-precipitation process, the in-situ recombination of the two can be achieved, the interaction between the two can be strengthened, the contact resistance between the two structures in the heterojunction can be reduced, the transport of carriers can be accelerated, and the catalytic performance of the heterojunction can be improved.

[0014] (2) Grinding the dried product into powder, calcining and decomposing it to obtain a layered catalyst.

[0015] Furthermore, the calcination temperature is 300-500° C., and the calcination time is 3-5 hours.

[0016] Furthermore, the calcination is carried out in a tubular furnace under a nitrogen atmosphere at a heating rate of 3-5°C / min to 300-500°C.

[0017] After calcination, Sn(OH)2 decomposes into SnO 2-x By controlling and adjusting the mass ratio of Na2C2O4 to SnCl2·2H2O and the mass ratio of g-C3N4 to SnCl2·2H2O, the abundance of oxygen vacancies in SnO2 can be regulated. Therefore, strictly speaking, the tin oxide in the heterojunction obtained in the present invention is no longer SnO2, but SnO 2-x The appropriate amount of oxygen vacancies is beneficial to the adsorption and activation of reactant molecules in the heterojunction.

[0018] Compared with the prior art, the present invention uses a coprecipitation method combined with thermal annealing treatment to obtain an in-situ composite of a two-dimensional pn-type heterojunction catalyst composed of a sheet-like g-C3N4 and a layered tin oxide. The obtained heterojunction structure has a low contact resistance and a large specific surface area. It provides an additional built-in electric field to accelerate the migration rate of carriers and improve the efficiency of photogenerated charge separation. The p-type and n-type semiconductors are both two-dimensional layered structures, which increase the carrier diffusion channel while providing more active sites and reaction sites for the adsorption and activation of C=O bonds. At the same time, by adjusting the raw material ratio, oxygen vacancies are created in tin oxide and its abundance is regulated to optimize its adsorption and activation of the catalyzed reactant molecules. Under the photoelectric coupling energy field, the catalyst can catalytically reduce CO2 to synthesis gas, providing a new idea for the development of green, efficient and stable new heterojunction photoelectric catalysts and the expansion of application fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0020] Figure 1 a is a scanning electron microscope image of the g-C3N4 nanosheet prepared in Example 1, Figure 1 b is SnO prepared in Example 1 2-x / SEM image of g-C3N4 full two-dimensional heterojunction catalyst;

[0021] Figure 2 Pure SnO and g-C3N4 and SnO prepared in Example 1 2-x / g-C3N4 full two-dimensional heterojunction catalysts. DETAILED DESCRIPTION

[0022] As used herein:

[0023] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0024] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0025] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0026] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0027] The test conditions for the photoelectrocatalytic reduction of CO2 directional conversion performance of the catalysts obtained in the following examples are as follows: AM1.5G (simulated sunlight), light intensity 100mW / cm 2 A high uniformity xenon lamp was used as the light source. High purity CO2 was introduced into the 0.1M Na2SO4 electrolyte for 30 min to saturate it. 2) was used as the counter electrode, the prepared catalyst was used as the photocathode, and the saturated Ag / AgCl electrode was used as the reference electrode in a three-electrode system. Under light conditions, a negative bias of -1.5 V (vs. Ag / AgCl) was applied to carry out photoelectrocatalytic reduction of carbon dioxide for 4 h.

[0028] Example 1

[0029] A method for preparing a heterojunction photoelectric catalyst comprises the following steps: weighing 20 g of urea, placing the urea in an alumina crucible with a lid, heating the crucible to 500° C. at a heating rate of 5° C. / min in an air atmosphere, maintaining the temperature for 4 hours, cooling the crucible, and grinding the crucible to obtain a light yellow powder g-C3N4.

[0030] 0.3 g g-C3N4 was weighed and placed in 30 mL of deionized water, followed by ultrasonication for 30 min to obtain solution A; 1.8 g SnCl2·2H2O was weighed and dissolved in 1.2 mL of concentrated hydrochloric acid, and 1.5 g Na2C2O4 was dissolved in 57 mL of deionized water, and the two were mixed and stirred to obtain solution B; solution A was slowly added to solution B, stirred for 30 min, and the product was centrifuged and washed with deionized water and anhydrous ethanol for 3 times each, and vacuum dried at 60 ° C for 10 h; the product obtained after drying was ground into powder, and heated to 350 ° C at a heating rate of 5 ° C / min in a tube furnace under nitrogen atmosphere and maintained for 2 h to obtain a full two-dimensional pn heterojunction SnO 2-x / g-C3N4.

[0031] The prepared g-C3N4 nanosheets and SnO 2-x / g-C3N4 fully two-dimensional heterojunction catalysts are Figure 1 In Figure 1 a and Figure 1 As shown in b.

[0032] like Figure 2 As shown in Figure 2, tin oxide and g-C3N4 were successfully composited to obtain a fully two-dimensional heterojunction catalyst SnO 2-x / g-C3N4.

[0033] Example 2

[0034] A method for preparing a heterojunction photoelectric catalyst comprises the following steps: weighing 20 g of urea, placing the urea in an alumina crucible with a lid, heating the crucible to 520° C. at a heating rate of 5° C. / min in an air atmosphere, maintaining the temperature for 3 h, cooling the crucible, and grinding the crucible to obtain a light yellow powder g-C3N4.

[0035] 0.3 g g-C3N4 was weighed and placed in 30 mL of deionized water, followed by ultrasonic treatment for 50 min to obtain solution A; 1.2 g SnCl2·2H2O was weighed and dissolved in 0.8 mL of concentrated hydrochloric acid, and 1.0 g Na2C2O4 was dissolved in 38 mL of deionized water, and the two were mixed and stirred to obtain solution B; solution A was slowly added to solution B, stirred for 40 min, and the product obtained by centrifugation was washed twice with deionized water and anhydrous ethanol, and vacuum dried at 80 ° C for 12 h; the product obtained after drying was ground into powder, and heated to 380 ° C at a heating rate of 5 ° C / min in a tube furnace under nitrogen atmosphere and maintained for 3 h to obtain a fully two-dimensional pn heterojunction SnO 2-x / g-C3N4.

[0036] Example 3

[0037] A method for preparing a heterojunction photoelectric catalyst comprises the following steps: weighing 20 g of urea, placing the urea in an alumina crucible with a lid, heating the crucible to 550° C. at a heating rate of 5° C. / min in an air atmosphere, maintaining the temperature for 2 h, cooling the crucible, and grinding the crucible to obtain a light yellow powder g-C3N4.

[0038] 0.3 g g-C3N4 was weighed and placed in 30 mL of deionized water, followed by ultrasonic treatment for 60 min to obtain solution A; 2.4 g SnCl2·2H2O was weighed and dissolved in 1.6 mL of concentrated hydrochloric acid, and 3.4 g Na2C2O4 was dissolved in 128 mL of deionized water, and the two were mixed and stirred to obtain solution B; solution A was slowly added to solution B, stirred for 60 min, and the product was centrifuged and washed with deionized water and anhydrous ethanol for 3 times each, and vacuum dried at 70 ° C for 11 h; the product obtained after drying was ground into powder, and heated to 400 ° C at a heating rate of 5 ° C / min in a tube furnace under nitrogen atmosphere and maintained for 4 h to obtain a full two-dimensional pn heterojunction SnO 2-x / g-C3N4.

[0039] The reduction products obtained from the photoelectrocatalytic reduction of CO2 directional conversion performance test of pure g-C3N4, pure SnO and the catalysts obtained in Examples 1-3 are shown in Table 1.

[0040] Table 1 Fully two-dimensional pn heterojunction SnO 2-x Comparison of performance of photoelectric reduction of CO2 to produce syngas by g-C3N4

[0041]

[0042] It can be seen that the full two-dimensional pn heterojunction SnO 2-xIn the synthesis gas produced by the / g-C3N4 photoelectrocatalyst, the ratio of CO to H2 is significantly different. By using the heterojunction catalyst of the present invention, the ratio of CO to H2 in the synthesis gas can be adjusted, and the selectivity and yield of CO are greatly improved.

[0043] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.

Claims

1. A method for preparing a heterojunction photoelectric catalyst, characterized in that: The steps include: (1) dissolving Na2C2O4 in deionized water and dissolving SnCl2·2H2O in concentrated hydrochloric acid, and then mixing the two to obtain a mixed solution; adding an aqueous solution of g-C3N4 to the mixed solution under stirring for 0.5-1 h to perform coprecipitation; washing and drying the precipitated product; (2) Grinding the dried product into powder, calcining and decomposing to obtain SnO 2-x / g-C3N4 layered catalyst; The g-C3N4 is prepared by calcining urea at 400-550°C for 2-4h, followed by cooling and grinding; The mass ratio of Na2C2O4 to SnCl2·2H2O is (2-5):3; The mass ratio of g-C3N4 and SnCl2·2H2 is 1:(2-6).

2. The preparation method according to claim 1, characterized in that: In step (1), the aqueous solution of g-C3N4 is obtained by dissolving g-C3N4 in deionized water and uniformly dispersing it by ultrasonication.

3. The preparation method according to claim 1, characterized in that: In step (1), the washing is performed by washing with deionized water and anhydrous ethanol several times.

4. The preparation method according to claim 1, characterized in that: In step (2), the calcination temperature is 300-500° C., and the calcination time is 3-5 hours.

5. The preparation method according to claim 1, characterized in that: In step (2), the calcination is carried out in a tubular furnace under a nitrogen atmosphere at a heating rate of 3-5°C / min.

Citation Information

Patent Citations

  • Porous carbon nitride / tin / stannous oxide photocatalytic material and preparation method thereof

    CN110743598A

  • Two-dimensional g-C3N4 nanosheet / SnO2 octahedral nanoparticle heterojunction photocatalyst and preparation method thereof

    CN113751045A

  • Preparation method of novel flower-like SnO2 / g-C3N4 heterojunction photocatalyst

    CN112007632A